Keabsahan Permohonan Pailit dan PKPU oleh Pekerja sebagai Alternatif Penyelesaian Kegagalan Pembayaran Upah - Fanny Gresta Nova (Fakultas Hukum Universitas Surabaya, 2024)
The increase in bankruptcy and The Suspension of Debt Payment Obligations (PKPU) cases in Indonesia occurs due to the failure to pay by the company, such as non-payment of debts to creditors or non-payment of workers' rights due to the company's declining financial situation. In addition, the increase in bankruptcy and The Suspension of Debt Payment Obligations cases is also supported by the requirements for filing bankruptcy applications which are very easy to fulfill. In the event that the debtor is a company, the applications for bankruptcy declaration can also be filed by workers because workers can be referred to as preferred creditors because wages and rights that have not been received by workers are debts that take precedence in payment. However, in relation to the failure to make payments by employers for wages or workers' rights, the applications for bankruptcy declaration by workers should be used as an ultimum remedium(the last resort), namely as a last resort for resolving the problem because if there is an industrial relations dispute between workers and company related to non-payment of wages or workers' rights, the state has provided legal remedies through the mechanism of Industrial Relations Dispute Settlement (PPHI). Based on this, the purpose of this paper is to find out whether the failure or inability of the company to make payments of wages or workers' rights can be resolved through the bankruptcy or The Suspension of Debt Payment Obligations instrument whereas as we know that rights disputes in labor disputes should be resolved through the Industrial Relations Dispute Resolution mechanism as stipulated in Law Number 2 of 2004 concerning Industrial Relations Dispute Resolution.